Analysis of Human Resource Competency in Improving Employee Performance in The Department Communication and Informatics of Gunungsitoli City - Nidasari Lase; Sukaaro Waruwu; Meiman Hidayat Waruwu; Robin Markus Putra Waruwu (PT. Maju Malaqbi Makkarana, 2025)
This study aims to analyze human resource competencies in improving employee performance at the Communication and Information Agency of Gunungsitoli City. Employee competencies, both in terms of technical knowledge, communication skills, and work attitudes, are important factors in determining the success of implementing government duties, especially in the digital era and the implementation of the Electronic-Based Government System (SPBE). This study uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results show that most employees have adequate technical skills in operating information technology devices, and demonstrate discipline and responsibility in carrying out their duties. The Communication and Information Agency has also exceeded several strategic performance targets, including improving digital services, public participation, and increasing the SPBE index value. This study recommends the importance of increasing regular training, updating digital infrastructure, and strengthening the competency-based performance evaluation system. Overall findings indicate that the development of HR competencies has a significant contribution to achieving effective, efficient, and adaptive institutional performance to the demands of the digital era.